Benefits from, Satisfaction with, and Self-Efficacy for Advanced Digital Hearing Aids in Users with Mild Sensorineural Hearing Loss - Johnson, Carole E.; Jilla, Anna Marie; Danhauer, Jeffrey L.; Sullivan, J. Connor; Sanchez, Kristin R. (Seminars in Hearing, 2018)
Little evidence is available regarding outcomes of advanced digital technology (ADT) hearing aid wearers with mild sensorineural hearing loss (MSNHL). The purpose of this article is to report the characteristics of and outcomes for this population. A cross-sectional research design was employed with 56 participants from a private practice setting. The International Outcomes Inventory for Hearing Aids (IOI-HA), Satisfaction with Amplification in Daily Life (SADL), and the Measure of Audiologic Rehabilitation Self-Efficacy for Hearing Aids (MARS-HA) were completed, scored, and compared with normative data. Results revealed that ADT aids were worn 10.5 hours/day, were mostly advanced to premium (55%), had an average cost per aid of $2,138 (SD = $840), and provided significant benefit (IOI-HA overall score: mean = 4.1; SD = 0.6) and satisfaction (SADL global score: mean = 5.4; SD = 0.8) to users who had good overall self-efficacy (MARS-HA composite score: mean = 81.7; SD = 12.8). Patients were most dissatisfied with and had the least self-efficacy for managing background noise and advanced handling of their devices. ADT hearing aid users with MSNHL achieved excellent outcomes, but ongoing follow-up and counseling from hearing health care providers may be important for successful management of background noise and mastery of advanced handling skills.
Keywords: mild hearing loss; adults; advanced digital hearing aids